Implementasi Aplikasi Edukasi Prakonsepsi Berbasis Web Untuk Meningkatkan Literasi Kesehatan Reproduksi Calon Pengantin di KUA Sidoarjo - Winda Nur Musfiroh Agustin; Bima Ardiyanto Wibowo; Yuninda Loviana Ersianti (Karya Kesehatan Journal of Community Engagement, 2026)
The preconception period is a crucial phase in preparing for a healthy pregnancy, as women’s physical, mental, and reproductive health conditions before conception greatly influence pregnancy outcomes and infant health. However, reproductive health literacy among prospective brides and grooms at the Religious Affairs Office (KUA) of Sidoarjo District remains low, while the existing educational process is still dominated by limited face-to-face counseling and less engaging printed materials. This Community Service Program (PKM) aimed to improve reproductive health literacy among prospective brides and grooms through the implementation of a web-based preconception education application. The program applied a community-based education approach through interactive lectures, application demonstrations, discussions, and evaluation using pre-test and post-test. The educational materials covered basic concepts of preconception care, premarital nutrition, risk factor detection, pre-pregnancy health screening, and healthy pregnancy planning. The activity was conducted on April 15, 2026, at KUA Sidoarjo District and involved 30 participants. The results showed a significant increase in knowledge, with the average pre-test score rising from 36.33 to 90.83 in the post-test, indicating an average improvement of 54.50 points. The mean N-Gain score was 0.848, which falls into the high category. In addition, the distribution of knowledge levels changed substantially: all participants were initially in the poor category during pre-test, while after the intervention, 96.7% were in the good category and 3.3% in the fair category. This program demonstrates that the web-based preconception education application is effective in improving the knowledge and reproductive health literacy of prospective brides and grooms. The activity also contributes to supporting couples’ readiness for family life and healthy pregnancy planning.